Student’s Preparedness and Their Clinical Performance in Psychiatric and Mental Health Nursing - Dela Rosa, Ronnell D.; Maniago, Jestoni D. (European Scientific Journal, ESJ, 2018)
This study determined the level of preparedness of student nurses of Manila Tytana Colleges Philippines, school year 2014-2015 in terms of knowledge, skills and attitude and its relationship with their clinical performance during their psychiatric rotation. Survey questionnaire and clinical evaluation tool appraisal were utilized to gather data from the 181 respondents selected through purposive sampling. Ethical clearance was secured from the institutional review board. The statistical tools used were mean, frequency and percentage distribution, and Pearson r. The results revealed that preparations in knowledge, skills and attitude in psychiatric clinical rotation doesn’t guarantee learning success in their psychiatric clinical duty. There was no significant relationship between the level of students’ preparedness and their clinical performance in psychiatric and mental health nursing (r value: 0.20; sig: 0.863). Thus, it was recommended that a similar study in the future would be conducted in other schools for validation of the findings. Also a qualitative study was recommended to assess further the best practice of the student in the psychiatric rotations including quality health care delivery in the said undertakings.